Evaluation of histopathological patterns in kidney disease: an overview from a tertiary health care center - Shraddha Goswami; Sharada C. Aher; Riyaz Asad; Ankit Jain; Snehal Mishra (International Journal of Advances in Medicine, 2026)
Background: The clinical manifestation of renal pathologies exhibits considerable heterogeneity. The incidence of kidney diseases is not only region-specific but also varies within different locales of the same country. This study was undertaken at a tertiary care hospital in central India to know the prevalence of various kidney diseases. The lack of a comprehensive national registry in India hampers the ability to compile detailed documentation of the diverse clinical presentations and histopathological characteristics of renal conditions nationwide. Consequently, this study aims to provide a histopathological diagnosis of kidney diseases proved by biopsy results. Methods: We collected demographic profile and native kidney biopsy reports of 154 patients who underwent kidney biopsy from January 2022 to January 2024 in the Department of Nephrology at our tertiary health care. Results: A total of 154 native kidney biopsies were analyzed, mean age was 33.58±15.79 years. The most common clinical presentation and indication for renal biopsy was nephrotic syndrome (59.74%). Most common histological pattern was primary glomerular disease in 92 (62.33%), followed by secondary glomerular in 26 (16.88%). The leading histopathological diagnoses were FSGS (18.8%) in >18 years and MCD (33.33%) in <18 years of age. MN and IgAN in 10.38% patients. Conclusions: The predominant indication for renal biopsy in our cohort was nephrotic syndrome. The spectrum of renal diseases varies by geographic location and is subject to temporal fluctuations. Consequently, the establishment of a renal biopsy registry is imperative for monitoring the evolving patterns of renal pathologies in India.